Scattered in times of the economy of attention: technology and us - Noronha, Ana Carolina Cortez [UNESP] (FapUNIFESP (SciELO), 2024)
The aim of this essay is to provide some reflections on the effects of the excessive use of technology today and how this affects contemporary subjects and their capacity for complex thinking and learning in and out of school. These reflections are based on issues situated at the intersection of technology and the human sciences, such as the over-stimulation and continuity brought about by the use of digital technologies, which clash with the need for stillness and deceleration for learning and complex reasoning. The intensified use of digital technologies that we are experiencing affects the functioning of the brain and disperses attention, which has been identified as the main contemporary asset - hence the term attention economy has emerged to replace information economy. It also reflects on the role of schools in guiding their students through this paradigm shift.
Dispersos em tempos de economia da atenção: a tecnologia e nós
Keywords: Attention; Hyperconnectivity; Information economy; Technology and Education